Dwelling Quality Assessment During Covid-19 Pandemic Self Isolation in East Jakarta - Afandi, Aisyah Arimurti (Cities and Urban Development Journal, 2023)
Background: The government encouraged public health protection with self isolation policy as an effort to control Covid-19 on a wide scale and prevent an increase in occupation rate on health service facilities in order to quickly and effectively handling confirmed cases of Covid-19. Dwelling quality is a significant factor to ensure that self isolation can be carried out effectively since it is stated in public health theory that one of the factors that influences a person's health status is dwelling quality. Aims: This research aims to assess dwelling quality where self-isolation being carried out during Covid-19 in East Jakarta. Methods: This research was conducted using qualitative research based on primary data sources collected through interviews, observation, and documentation. This research used non-probability sampling and snowball sampling, technique. Results: The findings in this research indicate that dwelling in East Jakarta do not meet several qualification related to building density, components and spatial arrangement, air circulation and natural lighting, as well as the house yard. Conclusion: Dwelling in East Jakarta where self isolation being carried out during Covid-19 pandemic are considered to be underqualified.